Avaliação de medidas cefalométricas em imagens obtidas a partir da telerradiografia de perfil e da tomografia computadorizada cone beam - Onofre, Niége Michelle Lazzari de (2013)
Introduction: The aim of this study was to evaluate the reproducibility and to compare the cephalometric measurements in images from conventional lateral radiographs (CLR) and in images synthesized from cone beam computed tomography (CBCT). Methodology: Twenty patients who had both a CBCT and a conventional lateral radiograph were recruited. Three observers digitized landmarks used for 10 measurements in CBCT images and in CLR from all patients at two different times (T1 and T2). The cephalometric analyses were conducted on the Radiocef Studio 2 software (RadioMemory Ltda., Belo Horizonte, MG, Brazil). In order to asses the reproducibility of exams in each technique, the ICC was calculatedd for each cephalometric measurement in each of techniques investigated. Differences between the modalities in T1 and T2 were calculated used t-student test. To compare the measurements from the three observers, Friedman test was used. Statistical significance was defined as 5% (p≤0,05). Results: the ICC of all measurements were above 0.8 in both methods, except for Nperp-Pog (ICC=0.66) for the Observer 2. There were statiscally and clinicaly differences for the Co-A (5,59 mm), Co-Gn (8,2 mm) and ENA-Me (5,9 mm) measurements between the methods. Differences were also found for NPerp-Pog (1,17 mm) and EixoY (0,68º). Conclusion: the reproducibility was good for all the measurements in both methods. The significant differences between the modalities were shown in 5 of the 10 measurements analized in this study. Measurements from CBCT synthesized cephalograms are not similar to those based on conventional radiographic images.